2013
DOI: 10.1016/s2007-4719(13)70944-x
|View full text |Cite
|
Sign up to set email alerts
|

Resiliencia: Diferencias por Edad en Hombres y Mujeres Mexicanos

Abstract: En este estudio se examinan los niveles de resiliencia considerando diferencias de edad y sexo, por lo que se presentan datos provenientes de una muestra compuesta por 607 participantes divididos en cuatro grupos de edad: niños, adolescentes, adultos jóvenes y adultez media, hombres y mujeres todos de la ciudad de Toluca México, aplicándose el cuestionario de resiliencia de González Arratia (2011). Los resultados de los análisis factoriales exploratorios para cada tramo de edad, indican una estructura de tres … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 10 publications
(4 reference statements)
4
8
0
4
Order By: Relevance
“…However, sex was independent. A similar result was previously reported [15, 17, 2224, 40]. Although Palomar and Gomez [12] reported greater resilience in women than in men, Fuentes et al [41] reported more resilience in male adolescents using a resilience questionnaire developed by the authors.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…However, sex was independent. A similar result was previously reported [15, 17, 2224, 40]. Although Palomar and Gomez [12] reported greater resilience in women than in men, Fuentes et al [41] reported more resilience in male adolescents using a resilience questionnaire developed by the authors.…”
Section: Discussionsupporting
confidence: 85%
“…We expected that the level of resilience would be greater in persons with higher educational levels, older age and female sex [12, 2123]. This expectation was supported in relation to educational level; in accordance with previous studies, the strength of the association was low [12, 21, 22]. The relationship with age was very low: the greater the age, the greater the level of structure, according to our expectation [12, 2123].…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Previous studies [132,133] have obtained similar results to those that were obtained in this study when relating resilience to gender and age. More specific studies close to our object of study [16,27,47] also demonstrate the correlation between success and resilience.…”
Section: Career Success and Resiliencesupporting
confidence: 88%